GREEN TECHNOLOGIES: NEW OPPORTUNITIES IN ENVIRONMENTAL PROTECTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Green technologies, often referred to as clean or sustainable technologies, represent a crucial step toward balancing economic growth with environmental responsibility. In the face of global challenges such as climate change, rapid industrialization, and the depletion of natural resources, the adoption of ecofriendly innovations has become more urgent than ever. These technologies encompass a wide range of solutions, including renewable energy systems, waste reduction strategies, energy-efficient devices, smart city initiatives, and sustainable production methods. The application of green technologies not only reduces carbon emissions and pollution but also opens new economic opportunities